PENGARUH PENGGUNAAN HANDOUT TERHADAP MINAT BELAJAR SISWA PADA MATA PELAJARAN BIMBINGAN TIK DI SMPN 1 2X11 ENAM LINGKUNG - Rosa Amelia; Liza Efriyanti; Zulfani Sesmiarni; Hari Antoni Musril (KOLONI, 2022)
This research is motivated by the low interest and motivation to learn more about learning materials. Moreover, the lack of adequate sources of teaching materials makes it difficult for students to understand the material presented by the teacher. The low interest in students' learning in learning seen from the ability of students to understand the material presented has not been fully understood, this could be due to the lack of variety of learning media used by teachers, resulting in a lack of student interest when studying. This study aims to determine the effect of using handouts on student interest in ICT guidance subjects at SMPN 1 2x11 Enam Lingkung. The research method used is quantitative with the type of ex post facto research. The total population taken is 237 students. The sampling technique used in this study is proportionate stratified random sampling for the percentage used is 25% with the number of respondents as many as 64 students with 35 males and 29 females. Based on the results of the study, it shows that there is a significant effect between the use of handouts (X) on student learning interest (Y) based on the results of hypothesis testing with calculations using the product moment correlation formula, the rcount value is 0.680 while the rtable value is 0.244 with a significance level of 0.05. of 0.462 and the effect is 46.2%. Because rcount is greater than rtable, this means that (Ha) is accepted and the hypothesis (Ho) is rejected. This means that there is a fairly positive relationship between the use of handouts and students' interest in learning. Keywords: Handouts, Teaching Materials, Student Interests, ICT Guidance